Using the Plan-Do-Study-Act (PDSA) Model for Continuous Quality Improvement of an Established Simulated Patient Program - Sarah. E. Vordenberg; Michael A. Smith; Heidi L. Diez; Tami L. Remington; Jolene R. Bostwick (University of Minnesota Libraries Publishing, 2018)
Objective: To describe the use of a continuous quality improvement process for strengthening our simulated patient (SP) program and the initial steps that have been implemented.  Innovation: A workgroup that included five clinical faculty with significant experience working with SPs and a strong interest in improving the SP program was developed.  The Plan-Do-Study-Act model was used as it allowed for incremental quality improvement changes, in order to ensure a high-quality SP program designed to optimize student learning.  Data were gathered from students, SPs, and faculty. Opportunities for improvement were prioritized based on anticipated benefits and available resources.  Changes related to planning, implementation, and evaluation and feedback have been executed. Critical Analysis: Changes related to planning that were implemented included developing handbooks for SPs, faculty, and graduate student instructors, as well as material for students in order to better describe the program.  SPs are now referred to as "simulated" as opposed to "standardized" as part of a broader effort to clarify the purpose of SP interactions to students.  Streamlined rubrics have been piloted, including electronic rubrics for first year students.  SPs are being trained on fewer cases, in order to improve the training program.  When possible, activities now take place in one large classroom instead of many small classrooms to improve oversight.  Finally, additional feedback has been obtained from SPs via a retreat.  These changes have been well received by students, SPs, and faculty.    Next Steps: The collection of this data and initial quality improvement changes provided a basis for hiring a full-time employee who will: dedicate 50% of their time to programmatic assessment of the SP program, support faculty with logistics and training, and be the face of our program to the students and SPs. Further, formal quantitative and qualitative assessment of the SP program has begun.   Type:  Note